2015
DOI: 10.1001/jamaoto.2014.2700
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Otolaryngology Systematic Review Research Gaps

Abstract: The representation of otolaryngologic conditions in CDSR correlates poorly with DALY metrics. The results of this study may guide future research prioritization and allocation of funds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Chow, et al (2013) has also analyzed that it is important to know about the significance of medical survey related to different complications. Pederson et al (2015) has specifically indicated that it is important for the general public to be aware of the otolaryngologic diseases as it will result in the better therapeutic rates along with better survival rates. Therefore, it can be said that awareness of medical survey is necessary to enhance the quality of life and welfare of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chow, et al (2013) has also analyzed that it is important to know about the significance of medical survey related to different complications. Pederson et al (2015) has specifically indicated that it is important for the general public to be aware of the otolaryngologic diseases as it will result in the better therapeutic rates along with better survival rates. Therefore, it can be said that awareness of medical survey is necessary to enhance the quality of life and welfare of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a larger series intended to map all 291 diseases studied by GBD to representation in major research databases [19] , [20] , [21] , [22] . It would also be valuable to compare topic prioritisation in other databases to CDSR, such as the Database of Abstracts and Reviews of Effects (DARE), Medline, Health Systems Evidence, and Web of Science, to provide further insight into whether research priorities are appropriately matched to corresponding disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancers account for 5.7% of global cancer- related mortality, with a significantly higher mortality burden and subsequent economic loss in LMICs compared to high-income countries (HICs) [ 33 ▪ ]. Other OHNS conditions with high global burden of disease include upper respiratory infections, cleft lip/palate, head and neck trauma, pediatric foreign body, and deep neck space infections [ 34 ▪ , 35 , 36 ▪▪ ].…”
Section: Essential Equipment and Services For Ohns Carementioning
confidence: 99%
“…The Global OHNS Initiative is a global consortium of OHNS clinical providers, trainees, and researchers with a vision for “ universal access to high-quality, safe, timely, and affordable care for those with OHNS conditions ”. To begin defining the role of OHNS care within comprehensive health systems, the group previously used the Delphi methodology to identify a consensus of priority OHNS conditions and procedures which all national health systems should be capable of managing [ 35 ]. The initiative then used these findings to develop an expert-driven list of the minimal equipment necessary for the medical and surgical care of the priority conditions.…”
Section: The Global Otolaryngology–head and Neck Surgery Initiative: ...mentioning
confidence: 99%